THE EFFECT OF DISCOVERY LEARNING ON STUDENT’S LEARNING OUTCOMES IN READING COMPREHENSION TO THE ELEVENTH GRADE STUDENTS AT SMA NEGERI 1 BUNGKU TENGAH - Rumo, Siti Mulya; Nadrun, Nadrun; Usman, Sriati; Wahyudin, Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2025)
The objective of this research is to investigate the effectiveness of using discovery learning on students’ learning outcomes in Reading Comprehension to the eleventh grade students at SMA Negeri 1 Bungku Tengah. This research used a quasi-experimental research design. There are two groups, namely the experimental group and the control group who received a pre-test and post-test. The population of this study was class XI students of SMA Negeri 1 Bungku Tengah. The research sample used a simple random sampling technique. Class XI MIA 5, totaling 32 students, was the experimental group and Class XI MIA 1, totaling 32 students, was the control group. The experimental group was given treatment while the control group was not. The test results showed that the average score of the experimental group on the post-test was 79.75 greater than the average score of the control group on the post-test of 52.62. These results also show that the t-count of 2.53 is higher than the t-table of 1.670 and the hypothesis is accepted. In conclusion, the use of discovery learning method can improve students's learning outcomes in reading comprehension of the eleventh grade students of SMA Negeri 1 Bungku Tengah.